Correlation between N-Acetyltransferase 2 (NAT2) Polymorphism Genotype with Plasma Isoniazid (INH) Concentration in MDR TB Patients Receiving Short Regimen in West Sumatera - Mega Senja; Masrul Basyar; Yessy Susanty Sabri; Afriani Afriani (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: Isoniazid (INH) is one of the most potent TB drug. High dose INH is used in short regimen MDR TB drugs. The genetic polymorphism of NAT2 affects the acetylation status. Awareness of the patients’ acetylator status is important to determine the risk of toxicity, treatment failure and drug resistance. The aim of this study was to demonstrate NAT2 genotype association with INH plasma concentration after 2 hours of oral INH therapy. Methods: This was a cross sectional study of MDR TB patients who received short term combination therapy at RSUP Dr. M.Djamil Padang, Achmad Muchtar Hospital Bukittinggiand West Sumatra Pulmonary Hospital from September 2019 to February 2020. Patients were examined for NAT2 genotype and plasma INH concentration. The results of the plasma INH concentrations obtained were evaluated based on the NAT2 acetylator phenotype group.Results: The majority of the subjects weremen (62.5%), aged 40-64 years (50%), had the most common comorbid of diabetes mellitus (31.25%), were normoweight (75%) and had negative HIV status (93.8%). A total of 7 alleles consisting of 7 SNPs and 7 variations of the NAT2 genotype were found in MDR TB patients who received short-term therapy. The NAT2*12A alleles (56.25%) was the most common allele and was a fast acetylator. Based on the bimodal distribution, the median concentration of INH in the fast and slow acetylator were 1.25 µg/ml and 5.24 µg/ml, respectively. The median values of INH concentration based on the trimodal distribution for fast, intermediate, and slow acetylators were 1.25 µg/ml, 2.17 µg/ml and 5.24 µg/ml. Conclusion: There were no correlations between the type of NAT2 acetylator phenotype and plasma INH concentrations.